2001
DOI: 10.1002/ppul.1088
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of sublingual immunotherapy in children with asthma and rhinitis: A double‐blind, placebo‐controlled study

Abstract: To evaluate the efficacy of specific sublingual immunotherapy (SLIT), we enrolled 15 children with asthma and rhinitis (7 girls, 8 boys, mean +/- SD age of 11.7 +/- 3.3) allergic to house dust mite (HDM) into a double-blind, placebo-controlled study. After a run-in period, patients were randomized to receive either placebo (n = 7) or SLIT (n = 8) with a standardized Dermatophagoides pteronyssinus (D. pteronyssinus) + Dermatophagoides farinea (D. farinea) 50/50 extract. They received increasing doses up to 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
129
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(139 citation statements)
references
References 13 publications
6
129
1
3
Order By: Relevance
“…Bahçeciler et al 19 found similar results to those by Aydogan et al 18 with regard to sensitization to HMD. At the end of the study, there was a reduction in the use of nasal corticosteroids to control rhinitis symptoms in the SLIT group compared with the placebo group (p = 0.004).…”
supporting
confidence: 73%
“…Bahçeciler et al 19 found similar results to those by Aydogan et al 18 with regard to sensitization to HMD. At the end of the study, there was a reduction in the use of nasal corticosteroids to control rhinitis symptoms in the SLIT group compared with the placebo group (p = 0.004).…”
supporting
confidence: 73%
“…25,28 Five studies demonstrated significant improvement in rhinitis/ rhinoconjunctivitis scores with SLIT, compared with placebo, with moderate to strong magnitudes of effect. 33,34,[36][37][38] Four studies did not show significant improvement with SLIT, 25,26,29,32 and 1 of these favored placebo. 26 The strength of evidence is moderate that SLIT improves rhinitis symptoms.…”
Section: Rhinitismentioning
confidence: 97%
“…[22][23][24][32][33][34][35]37,38 Seven studies evaluated dust mite allergen. [22][23][24][32][33][34]38 The SLIT-treated children in the placebo-controlled studies demonstrated moderate to strong improvement in asthma symptoms. The risk of bias was low in 3 studies.…”
Section: Asthmamentioning
confidence: 99%
See 2 more Smart Citations